Deflation in Hong Kong SAR - Schellekens, Philip (IMF Working Papers; Working Paper ;, 2003)
This paper examines the causes of deflation in Hong Kong SAR, exploring whether it reflects a prolonged process of adjustment to cyclical shocks or whether it results from price equalization pressures arising from structural integration with mainland China. To gauge the relative importance of these factors, the paper provides both an econometric and a qualitative analysis of the price dynamics between Hong Kong SAR and Shenzhen, a neighboring city in mainland China. It finds that the role of price equalization as a source of deflation is minor. Deflation in Hong Kong SAR is best explained by successive cyclical shocks which have been amplified by balance-sheet and wealth effects.